2002
DOI: 10.1021/ja017734b
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Abietadiene Synthase Catalysis:  Stereochemistry and Stabilization of the Cryptic Pimarenyl Carbocation Intermediates

Abstract: Abietadiene synthase (AS) catalyzes the complex cyclization-rearrangement of (E,E,E)-geranylgeranyl diphosphate (8, GGPP) to a mixture of abietadiene (1a), double bond isomers 2a-4a and pimaradienes 5a-7a as a key step in the biosynthesis of the abietane resin acid constituents (1b-4b) of conifer oleoresin. The reaction proceeds at two active sites by way of the intermediate, copalyl diphosphate (9). In the second site, a putative tricyclic pimaradiene or pimarenyl(+) carbocation intermediate of undefined C13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
44
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 53 publications
4
44
0
Order By: Relevance
“…Recent work on abietadiene synthase (AgAS) from grand fir (Ravn et al, , 2002Peters et al, 2000Peters et al, , 2001Peters et al, , 2003 has dissected the mechanism of this bifunctional conifer di-TPS. AgAS is very similar to Norway spruce PaTPS-LAS and PaTPS-Iso, thereby making the recent findings relevant to the mechanisms of these two enzymes as well.…”
Section: Comparative Modeling Of Norway Spruce Tps Active Site Structmentioning
confidence: 99%
“…Recent work on abietadiene synthase (AgAS) from grand fir (Ravn et al, , 2002Peters et al, 2000Peters et al, , 2001Peters et al, , 2003 has dissected the mechanism of this bifunctional conifer di-TPS. AgAS is very similar to Norway spruce PaTPS-LAS and PaTPS-Iso, thereby making the recent findings relevant to the mechanisms of these two enzymes as well.…”
Section: Comparative Modeling Of Norway Spruce Tps Active Site Structmentioning
confidence: 99%
“…To date, only a handful of di-TPSs involved in diterpene resin acid biosynthesis have been characterized, with all of them originating from gymnosperm trees (2). A series of papers from Croteau, Peters, and coworkers (14,15,(19)(20)(21)(22)(23) studied an abietadiene synthase (AS) from Grand fir [Abies grandis (Ag)] to establish the general mechanism and specific features of this type of di-TPS. Two closely related di-TPSs identified in Norway spruce [Picea abies (Pa)] have 91% amino acid identity but nonoverlapping product profiles (5).…”
mentioning
confidence: 99%
“…1]. The (ϩ)-CPP then freely diffuses to a second active site (class I) in the C-terminal domain, containing the Mg 2ϩ -binding DDXXD motif that catalyzes the diphosphate ionization-initiated cyclization of (ϩ)-CPP to produce the C8-sandaracopimarenyl cation intermediate (21)(22)(23) (Fig. 1, routes a and c).…”
mentioning
confidence: 99%
“…7 Later mechanistic work with recombinant AgAS established the intermediacy of isopimarenyl + (5) intermediates in enzymatic production of abietadienes from copalyl diphosphate (CPP, 6). 4 In addition, AgAS has been shown to produce sandaracopimara-8(14),15-diene (7) as a minor component (∼2%) of its product output, 8 suggesting 7 as a potential stable intermediate. However, labeling studies demonstrated intramolecular proton transfer, 9 and 7 is not converted to abietadienes by AgAS, 2 indicating that if 7 is a true intermediate it is only transiently formed en route to abietadienes in the AgAS active site.…”
mentioning
confidence: 99%
“…4,13 In particular, the secondary carbocations are significantly closer to the pyrophosphate than the preceding tertiary carbocations (e.g., Scheme 1). Accordingly, we hypothesize that the introduced hydroxyl group, at the relevant position in either AgAS or the previously examined ent-kaurene synthases, simply acts to stabilize pimar-15-en-8-yl + intermediates long enough for deprotonation to occur.…”
mentioning
confidence: 99%